Potential drug-drug interactions in a Brazilian teaching hospital: age-related differences? - Daniela Oliveira Melo; Eliane Ribeiro; Sílvia Storpirtis (São Paulo State University (UNESP), 2016)
This study proposes to measure frequency and to characterize the profile of potential drug interactions (pDDI) in a general medicine ward of a teaching hospital. Data about identification and clinical status of patients were extracted from medical records between March to August 2006. The occurrence of pDDI was analyzed using the database monographs Micromedex® DrugReax® System. From 5,336 prescriptions with two or more drugs, 3,097 (58.0%) contained pDDI. The frequency of major and well document pDDI was 26.5%. Among 647 patients, 432 (66.8%) were exposed to at least one pDDI and 283 (43.7%) to major pDDI. The multivariate analysis identified that factors related to higher rates of major pDDI were the same age (p< 0.0001), length of stay (p< 0.0001), prevalence of hypertension [OR=3.42 (p< 0.0001)] and diabetes mellitus [OR=2.1 (p< 0.0001)], cardiovascular diseases (p< 0.0001) and the number of prescribed drugs (Spearman's correlation=0.640622, p< 0.0001). Between major pDDI, the main risk was hemorrhage (50.3%), the most frequent major pDDI involved combination of anticoagulants and antiplatelet drugs. Among moderate pDDI, 3,866 (90.8%) involved medicines for the treatment of chronic non-communicable diseases, mainly hypertension. In HU-USP, the profile of pDDI was similar among adults and elderly (the most frequent pDDI and major pDDI were same), the difference was only the frequency in either group. The efforts of the clinical pharmacists should be directed to elderly patients with cardiovascular compromise, mainly in use of anticoagulants and antiplatelet drugs. Furthermore, hospital managers should increase the integration between levels of health care to promote safety patient after discharge. Keywords: Drug interactions. Aged. Internal Medicine. Hospitals, University.   RESUMO Interações medicamentosas potenciais em um hospital escolar brasileiro: diferenças relacionadas à idade? O estudo tem por objetivo descrever o perfil de interações medicamentosas potenciais (IMP) na clínica médica de um hospital escola. Dados sobre a identificação e estado clínico dos pacientes foram extraídos de prontuários médicos, entre março e agosto de 2006. A ocorrência de IMP foi analisada empregando-se o banco de monografias Micromedex DrugReax® System. Das 5.336 prescrições, 3.097 (58,0%) continham IMP. A frequência de IMP graves e bem documentadas foi de 26,5%. Entre os 647 pacientes, 432 (66,8%) foram expostos a pelo menos uma IMP e 283 (43,7%) uma IMP grave. A análise multivariada identificou que os fatores relacionados a maiores taxas de IMP e IMP graves foram os mesmos: idade (p< 0,0001), tempo de internação (p< 0,0001), prevalência de hipertensão [OR=3,42 (p< 0,0001)] e diabetes mellitus [OR=2,1 (p< 0,0001)] , doenças cardiovasculares (p< 0,0001) e o número de medicamentos prescritos (correlação de Spearman =0,640622, p< 0,0001). Entre as IMP graves, o principal risco foi hemorragia (50,3%) e as IMP graves mais frequentes envolviam a combinação de anticoagulantes e agentes antiplaquetários. Entre as IMP de gravidade moderada, 3.866 (90,8%) envolviam medicamentos para o tratamento de doenças crônicas não transmissíveis, particularmente hipertensão. No HU-USP, o perfil de IMP foi similar entre adultos e idosos (as IMP e IMP graves mais frequentes foram as mesmas), a diferença estava apenas na diferença na frequência em cada um dos grupos. Os esforços dos farmacêuticos clínicos deveriam ser direcionados aos pacientes idosos, com comprometimento cardiovascular, principalmente aqueles em uso de anticoagulantes e fármacos antiplaquetários. Além disso, deve-se aumentar a integração entre os níveis do cuidado a saúde para promover a segurança do paciente após a alta. Palavras-chave: Interações de Medicamentos. Idoso. Medicina interna. Hospitais Universitários.